A CBT-based stress management module for police officers: A pre-post intervention study - Mohd Shahrul, Kamaruddin; Bong, Lai Mao; Tsai, Jia Hui; Jacklyn Ting, Min Ming; Amos Ting, Qi Tao (UNIMAS Publisher, 2026)
Despite the high-stress nature of policing roles in Malaysia, there is a lack of structured, evidence-based stress management interventions with measurable outcomes for police personnel. This study presents the outcomes of a stress management module conducted at the Kuching District Police Headquarters (IPD) to address occupational stress among Malaysian police personnel. Given the high-stress nature of policing roles, the intervention focused on equipping officers with mindfulness practices and time management techniques to foster psychological resilience, emotional regulation, and enhanced professional effectiveness. The program was designed to incorporate pre- and post-assessment tools to evaluate changes in stress awareness, stress coping strategies, and individual productivity. A total of 39 police officers initially participated in the program, of whom 36 completed the full intervention. Findings indicated measurable improvements in participants' ability to recognise personal stressors, apply mindfulness-based stress reduction techniques, and utilise structured time management to handle workload demands. These results underscore the value of incorporating structured wellness training into the professional development of police personnel in Malaysia and highlight the potential for broader institutional integration across district level law enforcement units.